Conversations on justice from national, international, and global perspectives : dialogues with leading thinkers / edited by Jean-Marc Coicaud, Lynette E. Sieger. - Coicaud, Jean-Marc; Coicaud, Jean-Marc; Sieger, Lynette E. (Cambridge University Press, 2019)
The question of what constitutes norms for global justice is of considerable concern for all those interested in world peace and cooperation. In order to define these global norms, Jean-Marc Coicaud, while working at the United Nations University, initiated a project centered around conversations with leading theorists and policy practitioners in global affairs. Conversations on Justice from National, International, and Global Perspectives features world-class authors and activists, from around the world, and from a variety of disciplines, to discuss the central questions of justice at the national, international, and global levels. Made up of a compilation of dialogues, this volume's unique format makes it highly accessible and even fun to read. The insights and observations of these leading intellectuals and scholars provide a rich contribution to theories on how global justice might become a reality.